Training Needs of Faculty Members at the University of Hail in the Light of Creative Teaching Skills - Seham Alsayed Saleh Murad, Jaleela Altayib Babiker Younis, Ashwaq Farag Suliman Altalal (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The current research aimed to determine the rate of training needs of faculty members at the University of Hail in the light of creative teaching skills. Design of the Study: It was a descriptive analytical method. Place and Duration of Study: This study was carried at the. Patients and Methods: The descriptive analytical approach was used, which is represented by a survey of literature, previous studies and tools for the subject of the research. and by applying it to a sample of faculty members at the University of Hail affiliated with the university’s faculties (in some practical and theoretical faculties) in the academic year 1442 AH / 2021 AD, the sample consists of 120 members. Results of the Study: Where the results of the research showed that all fields of training needs are necessary and important, and that the rate of training need for creative teaching skills in its five fields was high, ranging between (93.3℅ -98.10℅), and in light of these results, a proposed scenario was prepared for a training program to develop creative teaching skills among members.. Practical Implication: The groundwork and growth of Higher education institutions from all over the world arouse the curiosity of a professor. As a result of globalisation and technological advancement, they have begun working on programmes to improve his performance and efficiency, as well as creating an optimal environment for him to accomplish his duties. Conclusion: The research recommended the need to train faculty members to practice creative teaching in light of the requirements of distance education according to specialization, and to reorganize and formulate the content of specialization courses electronically in light of creative teaching skills. Research recommended the need to pay attention to the development of creative thinking skills among their students through creative activities and tasks. It also recommended; training them on teaching methods and strategies that help develop creative teaching skills, and methods of evaluating courses online, and a number of proposals were presented for future research. Keywords: Distance Education, Teaching Strategies, Calendar Methods, Electronic Courses